A bivalent antihypertensive vaccine targeting L‐type calcium channels and angiotensin AT1 receptors. (12th December 2019) - Wu, Hailang; Wang, Yiyi; Wang, Gongxin; Qiu, Zhihua; Hu, Xiajun; Zhang, Hongrong; Yan, Xiaole; Ke, Fan; Zou, Anruo; Wang, Min; Liao, Yuhua; Chen, Xiao
Abstract : Background and Purpose: Hypertension has been the leading preventable cause of premature death worldwide. The aim of this study was to design a more efficient vaccine against novel targets for the treatment of hypertension. Experimental Approach: The epitope CE12, derived from the human L‐type calcium channel (CaV 1.2), was designed and conjugated with Qβ bacteriophage virus‐like particles to test the efficacy in hypertensive animals. Further, the hepatitis B core antigen (HBcAg)‐CE12‐CQ10 vaccine, a bivalent vaccine based on HBcAg virus‐like particles and targeting both human angiotensin AT1 receptors and CaV 1.2 channels, was developed and evaluated in hypertensive rodents. Key Results: The Qβ‐CE12 vaccine effectively decreased the BP in hypertensive rodents. A monoclonal antibody against CE12 specifically bound to L‐type calcium channels and inhibited channel activity. Injection with monoclonal antibody against CE12 effectively reduced the BP in angiotensin II‐induced hypertensive mice. The HBcAg‐CE12‐CQ10 vaccine showed antihypertensive effects in hypertensive mice and relatively superior antihypertensive effects in spontaneously hypertensive rats and ameliorated L‐NAME‐induced renal injury. In addition, no obvious immune‐mediated damage or electrophysiological adverse effects were detected. Conclusion and Implications: Immunotherapy against both AT1 receptors and CaV 1.2 channels decreased the BP in hypertensive rodents effectively and provided protection against hypertensive target organ damage without obvious feedback activation of renin‐angiotensin system or induction of dominant antibodies against the carrier protein. Thus, the HBcAg‐CE12‐CQ10 vaccine may provide a novel and promising therapeutic approach for hypertension.